2015
DOI: 10.1016/j.ascom.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A compression scheme for radio data in high performance computing

Abstract: We present a procedure for efficiently compressing astronomical radio data for high performance applications. Integrated, post-correlation data are first passed through a nearly lossless rounding step which compares the precision of the data to a generalized and calibration-independent form of the radiometer equation. This allows the precision of the data to be reduced in a way that has an insignificant impact on the data. The newly developed Bitshuffle lossless compression algorithm is subsequently applied. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 23 publications
(26 reference statements)
0
47
0
Order By: Relevance
“…However, most results will be presented in as general form as possible to facilitate extensions. The covariance of the visibilities is (Kulkarni 1989;Masui et al 2015):…”
Section: Antennas and Visibilitiesmentioning
confidence: 99%
“…However, most results will be presented in as general form as possible to facilitate extensions. The covariance of the visibilities is (Kulkarni 1989;Masui et al 2015):…”
Section: Antennas and Visibilitiesmentioning
confidence: 99%
“…The public registry for HDF5 filters 1 currently lists 21 data transformations, most of them compression-related. Each HDF5 file is evaluated with and without the shuffle filter, zlib/gzip, lzf, MAFISC [22] with LZMA, szip [20], Bitshuffle [30] with LZ4, zstd, and the full Blosc [1] compression suite, again all with various parameter values.…”
Section: Data Representationmentioning
confidence: 99%
“…The algorithm will also have to look for correlations in the time direction, while time is generally the slowest changing dimension. It has been shown to provide good results thought (Masui et al 2015), and a combination of these methods might provide a generic algorithm that performs near-optimal in noise-dominated as well as signal-dominated situations.…”
Section: Possible Improvements and Future Workmentioning
confidence: 99%
“…-AIPS can write visibilities as 16-bit values with uniform quantization; -The Flexible Image Transport System (FITS) file format (Wells et al 1981) allows Rice, GZIP, HCompress, and PLIO compression 2 . -For compression of integer data recorded with the CHIME telescope, Masui et al (2015) showed that those data can be compressed to 28% of its original size using linear quantization and applying the BITSHUFFLE technique before LZ77 encoding (Ziv & Lempel 1977).…”
Section: Introductionmentioning
confidence: 99%